PEMBUDIDAYAAN JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) DENGAN MEDIA LIMBAH KAYU - Sihati Suprapti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Wood waste such as sawdust, leaves of legume plants such as turi (Sesbania grandiflora Pers.) and lamtoro gung (Leucaena leucocephala (Lam.) de Wit.) were used as substrates for oyster mushroom, Pleurotus ostreatus cultivation. The substrate consisted of rubber wood sawdust (Hevea brasiliensis Muell. Arg.) mixed with turi or lamtoro gung leaves containing 50%, 100%, 150%, 200%, by weight and distilled water. The substrate was allowed to cool after autoclave sterilization before being inoculated with pure culture oyster mushroom.The mushroom was harvested every day after the growth of the fruiting body. The average yield of the entire treatments was 643.00 g (532. 29- 744. 69 g) per kg of dry weight of substrate. The highest product was obtained from rubber wood sawdust substrate mixed with 10% turi leaf.